Effectiveness of Task-based Approach in Teaching Translation: A Study of Tanzanian Secondary EFL Classrooms - Kulwa Yohana Matalu (JELITA, 2024)
This research aimed at examining the activities used by teachers in teaching translation in English subject in Tanzanian high schools (also known as advanced secondary schools) and their effectiveness in enhancing translation competences to students. This study used qualitative approach with a case study design to collect data. The research subjects were 3 teachers and 60 students in 3 advanced secondary schools in Dodoma City. The students were grouped in small groups consisting of 4-5 students each who were tasked to translate or evaluate texts in the classroom. The data were collected through classroom observation and document review. The data were analyzed through conventional content analysis. The findings showed that the teachers tasked students to translate and back translate sentences, paragraphs, and evaluate them. These activities equipped students with lower order translation sub-competences such as bilingual, extralinguistic, and translation knowledge sub-competences as reflected in the model of translation competence suggested by Albir et al. (2020). Translating activities engage students in both hands-on and minds-on learning which prepares them for real-life translation activities.